TSG‐6 is weakly chondroprotective in murine OA but does not account for FGF2‐mediated joint protection - Zhu, L; Donhou, S; Burleigh, A; Miotla Zarebska, J; Curtinha, M; Parisi, I; Khan, SN; Dell'Accio, F; Chanalaris, A; Vincent, TL (Wiley, 2020)
Objective Tumor necrosis factor α–stimulated gene 6 (TSG‐6) is an anti‐inflammatory protein highly expressed in osteoarthritis (OA), but its influence on the course of OA is unknown.